2005
DOI: 10.1038/sj.cdd.4401599
|View full text |Cite
|
Sign up to set email alerts
|

The voltage-dependent anion channel-1 modulates apoptotic cell death

Abstract: The role of the voltage-dependent anion channel (VDAC) in cell death was investigated using the expression of native and mutated murine VDAC1 in U-937 cells and VDAC inhibitors. Glutamate 72 in VDAC1, shown previously to bind dicyclohexylcarbodiimide (DCCD), which inhibits hexokinase isoform I (HK-I) binding to mitochondria, was mutated to glutamine. Binding of HK-I to mitochondria expressing E72Q-mVDAC1, as compared to native VDAC1, was decreased by B70% and rendered insensitive to DCCD. HK-I and ruthenium re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
366
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(394 citation statements)
references
References 48 publications
(112 reference statements)
22
366
1
5
Order By: Relevance
“…In this study, the authors suggested that the effect of tBID on OMM permeabilization is through another unidentified OMM protein. The importance of VDAC for OMM permeabilization is further supported by recent evidence that overexpression of VDAC induces apoptosis in various cell types, and this effect is inhibited by BCL-2 and VDAC inhibitors [28,29].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 76%
“…In this study, the authors suggested that the effect of tBID on OMM permeabilization is through another unidentified OMM protein. The importance of VDAC for OMM permeabilization is further supported by recent evidence that overexpression of VDAC induces apoptosis in various cell types, and this effect is inhibited by BCL-2 and VDAC inhibitors [28,29].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 76%
“…Despite experimental observations supporting the models depicted in Figures 2 and 3, other investigators have recently suggested that hexokinase-mediated VDAC closure, rather than VDAC opening, may underlie the ability of hexokinases to inhibit apoptosis (Azoulay-Zohar et al, 2004;Zaid et al, 2005). This fundamentally different interpretation was inferred from the ability of HKI to decrease the in vitro conductivity of purified VDAC reconstituted into planar lipid bilayers by approximately 70% and is based upon the assumption that cytochrome c is released via VDAC (AzoulayZohar et al, 2004).…”
Section: Mitochondrial Hexokinases As Downstream Effectors Of Growth mentioning
confidence: 99%
“…Although still incompletely understood, a major landmark in our understanding of the molecular basis of hexokinasemitochondria interaction occurred about 25 years ago when a hexokinase-binding protein isolated from mitochondria (Felgner et al, 1979) was identified as VDAC (Fiek et al, 1982;Linde´n et al, 1982). Subsequent studies have clearly validated the notion that mammalian VDAC directly participates in the specific binding of mitochondrial hexokinases to the OMM (Nakashima et al, 1986;Vyssokikh et al, 2001;Azoulay-Zohar et al, 2004;Zaid et al, 2005). Unlike their mammalian counterparts, yeast hexokinases do not bind mitochondria, and yeast mitochondria do not bind hexokinases (Wilson, 1997b).…”
Section: Mammalian Cells Express Multiple Hexokinase Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there are several VDAC isoforms (VDAC1, VDAC2, VDAC3). Although there is no systematic study that has addressed the contribution of VDAC isoforms to apoptosis, it appears that VDAC1 is proapoptotic (Zaid et al, 2005), while VDAC2 might be antiapoptotic, acting as an endogenous inhibitor of Bak (Cheng et al, 2003).…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%